Motahhari and the Refutation of Idealism - Abdurrazzaq Hesamifar (حکمت معاصر, 2011)
Since 17th century, western philosophy experienced a basic change in philosophical research and discussing the formation of knowledge and its validity became the most important problem in philosophy. This change, however, was reflected in Islamic philosophy three century later, because there was no relation between these two worlds of philosophy. As a great expert in Islamic philosophy, Motahhari attempted at first to be informed of the ideas of the modern and contemporary philosophers and afterwards to review them. One of these ideas on which he was concerned, was the problem of knowledge. There are two counter views on perception and its representation. The first one is realism which affirms the existence of physical things as the objects of perception and thinks that the external world is represented in the perceptions. The other one is subjective idealism which denies this matter. In their The Principles of Philosophy and the Method of Realism, Tabatabaei and Motahhari by reliance on the realistic foundations of Islamic philosophy, criticize subjective idealism on the one hand and dialectic materialism on the other. Motahheri's view in this book which has been written in 1330s H. differs from his view in his Detailed Account of Manzoumeh which has been written in 1350s H. In the former book he regards idealism as equal to sophism and thinks of the idealist philosophers like Berkeley and Schopenhauer as equal to the sophists like Protagoras and Gorgias, because they all deny the external world, but in the later he presents some deeper analysis of the theory of knowledge and proving the existence of external world. In this paper Motahheri's views on epistemology and his critics against idealism will be discussed and reviewed.